Transformasi Digital dalam Politik dan Tata Kelola di Indonesia: Peluang dan Tantangan di Era Disrupsi Teknologi - Muhlis Hafel (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Digital transformation has become a major driver of change in politics and governance in Indonesia. This study aims to examine the opportunities and challenges faced in the process of digitalizing the public sector in Indonesia. Using a qualitative approach with case studies and literature analysis, the research identifies several key aspects, including increased political participation through social media platforms, the evolution of e-governance, and the implications of cybersecurity and data privacy. The units of analysis include policies and practices of digitalization in the public sector. The study population consists of government agencies, active politicians on social media, and citizens participating in digital politics. A purposive sampling technique was used to select key government agencies, influential politicians on social media, and digitally active citizens. Data were collected through in-depth interviews and document analysis and analyzed using thematic analysis techniques. The findings indicate that digital technology creates new opportunities to enhance transparency, efficiency, and public participation in Indonesian governance. However, challenges such as the digital divide, cybersecurity threats, and data privacy protection remain. The results highlight the importance of adaptive policies and robust regulatory frameworks to maximize the benefits of digital transformation while addressing existing challenges.